2004
DOI: 10.1097/01.ta.0000033140.73750.14
|View full text |Cite
|
Sign up to set email alerts
|

Management of Penile Fracture

Abstract: Penis fracture is a true urologic emergency. It should be treated surgically as early as possible to ensure a better outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
65
0
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 13 publications
1
65
0
4
Order By: Relevance
“…Current literature supports immediate surgical repair which have minimal complications and goog functional outcome. 15,16 No immediate complications were seen in the patients while as on follow up 2 (4.1%) had pricking sensation at repair site, 2 (4.1%) patients had mild penile deviation during erection toward rent side, but it did not affect their sexual activities and 1 (2.01%) patient had mild painful erection. Nawaz H et al found penile deviation in 4.3% of patients.…”
Section: Discussionmentioning
confidence: 98%
“…Current literature supports immediate surgical repair which have minimal complications and goog functional outcome. 15,16 No immediate complications were seen in the patients while as on follow up 2 (4.1%) had pricking sensation at repair site, 2 (4.1%) patients had mild penile deviation during erection toward rent side, but it did not affect their sexual activities and 1 (2.01%) patient had mild painful erection. Nawaz H et al found penile deviation in 4.3% of patients.…”
Section: Discussionmentioning
confidence: 98%
“…Penile fracture is described as the rupture of the tunica albuginea and/or corpus spongiosum in the erect penis caused by rapid blunt force [12]. The tunica albuginea, which has a normal thickness of 2 mm when the penis is flaccid, is stretched during erection and its thickness is reduced to 0.25 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Tras el examen clínico, el diagnostico más fiable se obtiene mediante Resonancia Magnética Nuclear 5,6 ya que permite establecer la integridad de la albugínea, lo que será fundamental de cara a plantear o no una exploración quirúrgica 7 . También permite el diagnóstico diferencial con tumoraciones derivadas de partes blandas como en el caso descrito.…”
Section: Discussionunclassified